Analisa Getaran Pada Air Fin Cooler Equipment 203-E-003-M4 Akibat Misalignment Poros - Samudra Budi Agung; Poernomo Heroe; Wirawan Husodo Adi (Proceedings Conference on Marine Engineering and its Application, 2018)
This research performs vibration response analysis on fin cooler water system (AFC). AFC is a fan or blade equipment that rotates and driven by the motor. AFC have problems of high vibration value, so disrupting the production process. From the case obtained the purpose of research to get the value of vibration response that occurs on the shaft of water fin cooler and the influence of misalignment on the shaft. From the vibration data, analyzed the breakdown that occurred. To prevent vibration and breakdown, failure evaluation with Predictive Maintenance method is performed. In the research, the result of natural frequency is 26,77 rad/s and vibration velocity response is 0,0000392 mm/s. Vibration rate response with 0.05 mm shaft misalignment of 0,0000496 mm/s is still permitted by ISO Severity 10618-3 standard. The result of AFC reliability at 24 hours cause a reliability value of 0.995. Then the failure prediction of AFC component will occur at 15773,42 hours or 657 days, then result of the calculation of treatment time after further analysis using dynamic system predicted to be done within 1738 hours or 72 days.